Comparison of the Actim Partus test and the fetal fibronectin test in the prediction of spontaneous preterm birth in symptomatic women undergoing cervical length measurement. (November 2016) - Bruijn, Merel M.C.; Vis, Jolande Y.; Wilms, Femke F.; Oudijk, Martijn A.; Kwee, Anneke; Porath, Martina M.; Oei, Guid; Scheepers, Hubertina C.J.; Spaanderman, Marc E.A.; Bloemenkamp, Kitty W.M.; Haak, Monique C.; Bolte, Antoinette C.; et al.
Abstract: Objective: To compare the accuracy of the Actim Partus test and fetal fibronectin (fFN) test in the prediction of spontaneous preterm delivery within seven days in symptomatic women undergoing cervical length measurement. Study design: We performed a post-hoc analysis on frozen samples of a nationwide cohort study in all 10 perinatal centres in the Netherlands. We selected samples from women with signs of preterm labour between 24 and 34 weeks of gestational age and a cervical length below 30 mm. Delivery within seven days after initial assessment was the primary endpoint. We calculated sensitivity, specificity, and positive and negative predictive values for the combination of both the Actim Partus test and fFN test with cervical length. A test was considered positive in case of a cervical length between 15 and 30 mm with a positive Actim Partus or fFN test, and a cervical length below 15 mm regardless the test result. Results: In total, samples of 350 women were tested, of whom 69 (20%) delivered within seven days. Eighty-four women had a positive Actim Partus test and 162 women a positive fFN test, of whom 54 (64%) and 63 (39%) delivered within seven days, respectively. Ninety-seven women had a cervical length below 15 mm, of whom 50 (52%) delivered within seven days. Sensitivity, specificity, positive and negative predictive values of combining cervical length with the Actim Partus test or the fFN test were 91%, 75%, 47% and 97%, and 96%, 58%, 36% and 98%, respectively. Conclusion: According to this post-hoc study, in combination with cervical length, the Actim Partus test could be used as an alternative for the fFN test to identify women who will not deliver within seven days after presentation. Further evidence should be collected in a prospective comparative study.